Relationship Between Perception of Service Quality in the Emergency Room and the Level of Anxiety of Patient Family - Fredita Andriana Putri; Ekan Faozi (GLOBAL HEALTH SCIENCE GROUP, 2025)
Anxiety is a problem that arises in families when caring for patients in the ER due to emotional stress felt in emergencies. This anxiety occurs due to changes in roles, unfamiliar hospital environments, and perceptions of service quality. Family members of patients who experience anxiety will affect their role in family support. Family support is essential in increasing enthusiasm and encouraging patients to recover. The purpose of this study was to examine the relationship between perceptions of service quality in the ER and the level of anxiety of patient families. The research design used descriptive correlation with a cross-sectional study approach. The sampling technique was accidental sampling. The number of samples was 99 according to the inclusion and exclusion criteria that had been determined. Data collection in the study used the SERVQUAL questionnaire model on family perceptions of service quality and the Zung Self-Rating Anxiety Scale (ZSAS) to assess anxiety levels. Bivariate analysis used the Spearman's test. The statistical test results obtained p <0.05 (p-value = 0.001), namely, there is a relationship between perceptions of service quality in the emergency installation and the level of anxiety of patient families at RSUD Ir. Soekarno Sukoharjo. The higher the family's perception of service in the emergency room, the lower the level of anxiety they have.